Space of Faculty Formation: History of Education classes - Almeida, Doris Bittencourt (Education Policy Analysis Archives, 2013)
The text discusses the meaning of history of education as a curricular subject present especially in pedagogy courses, taking in consideration its relevance in the process of faculty formation. The History of Education, in its double identity, subject and researching area, is located in a border zone, at times approaching History, at times Education. The narrowing of these dialogues relies on Cultural History, as contemporary historiographical trend that contributes to the renewal of Western historiography. Throughout the article argues the importance of thinking about History of Education classes that delight students, seeking to value their knowledge, yearnings and ancestries, therefore, being linked to the educational experiences and realities of the country in its contemporaneity. In this sense, the classes should seek to answer questions that depart from the context in which we live so that each student can reflect and achieve effective and affective meanings attributed to this discipline.